(3bhGYO GdCMcGe aj eSGFd GdMdGd hGdMQGes - (3GdejSj, , GdejSj, GdejSj, dWa Gddg Hf YHO GdcQje Hf EHQGgje Hf Ydj, J (B1032(3g` (B1623(3es
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdYdj GdcHjQ GdMcje GdNHjQ GdYdje GdbOjQ(B... (3Ke TQYJ aj TQM Whjd jTJed ef GdebGUO Ydi cd Objb hLdjds
(3BNQgG (B:s
(3BNQgG(B: (3bhdg aEf GdejJ dG bhd dg hEf cGf eLJgkOG eeG jOd Ydi Pdc Cf GdGLeGY dG jfYbO eY NdGag MjG hjfYbO HYO ehJg hdG jYJO HNdGag, bhdg(B: (3hdG jLhR GQJcGHg hEf NGa GdJda XGgQg jefY Ef NGa GdbJd HWQjb CTOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 242s
(3GdPQjYI, L (B5: 51s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis